Estudo químico de Alternaria alternata patótipo tangerina em meio artificial e na interação com Guignardia citricarpa - Prieto, Kátia Roberta (2012)
The study of phytopathogenic fungi Alternaria alternata has improved the chemical of this micro-organism. The fungus was grown up in large scale incubated in rice medium for 26 days. After grown period was interrupted an extract of the microorganism was made and fractionated using several chromatographic techniques, obtaining 11 different classes of metabolites which are: alternariol monomethyl éter, alternariol, altertoxin, altenuen, altenusin, uridine, uracila, 5 -inosil, ergosterol, peróxido de ergosterol e triglycerides. Also, a study was made via LC-MS in order to identify some toxins produced by A. alternata like a pathogen of citrus, and it was possible to identify four of these. Other research via LC-MS was the study of co-cultivation of the fungus A. alternata, the causal agent of alternaria brown spot, and Guignardia citricarpa, the causal agent of citrus black spot. In this study was possible to observe the variation in concentration of alternariol and thenuazonic acid, mycotoxins produced by A. alternata when this fungus is in contact with G. citricarpa. The study identification of the volatiles produced by A. Alternaria in different ways contributed significantly to improve the knowledge of their chemistry. Once, the A. alternata is a pathogenic fungus of 'Murcott' a study was performed via scanning electron microscopy (ESEM). Thus it was possible to observe the penetration of this fungus by stomatal cavity of young leaves of citrus. In order to search for natural inhibitors to control the disease, were tested several classes of natural products against the A. alternata, and some alkaloids, a xxvi coumarin, a xanthyletin, and a flavonoid substances showed Higher inhibition of mycelial growth, spore germination and appressorium formation. With the aim to obtain information on natural inhibitors were tested metabolites produced by A. alternata opposite and G. citricarpa, the results indicated that alternariol monomethyl ether and alternariol were substances that had a potential fungistatic against the causal agent of citrus black spot.